SUFIZADA - INDIVIDUAL IMAGE AND SKILL - Gulnavoz Mamadaliyeva (Western European Studies, 2024)
In this article, Muhammadsharif Sofizoda's individual image and skills are covered by studying examples of his work. Also, after reading the article, you will be convinced once again that the poet is the owner of high spirituality and enlightenment.
Keywords: individual; ideal; musaddas